THE POSITION OF AL-‘URF AS LEGAL ARGUMENT - Siregar, Bismar; Asmuni, Asmuni; Syahnan, Muhammad (Universitas Islam Negeri Sumatera Utara Medan, 2024)
Úrf is a custom or practice that occurs among communities and is in accordance with the requirements of the Qur'an and Hadith, so that it can be used as a legal argument. The purpose of this study is to identify the practices carried out by many people (groups) that arise from creativity or imagination in building cultural values. This research is a library research study, which focuses on the analysis and interpretation of secondary data obtained from various sources, such as books, articles, and other documents. This study also uses a qualitative research approach, which focuses on a deep understanding of the phenomenon being studied. This study uses a hermeneutic research approach, which focuses on the interpretation and analysis of 'urf as something that is considered good by society. This approach allows researchers to understand the context and meaning associated with urf and how it is used as a basis for legal decisions. This study uses primary and secondary data sources. The primary data sources used are the Qur'an and Hadith, which are the main sources of law in Islam. The secondary data sources used are books, articles, and other documents related to the position of urf as a source of law